Studi Literatur Proses Metakognisi dalam Pemecahan Masalah Matematika - Siolimbona, Dedi Rahman; Juniati, Dwi; Khabibah, Siti (Universitas Dr. Soetomo, 2023)
Abstract This article aims to describe mathematical problem-solving and its relation to the process of metacognition. This study focuses on mathematical problem-solving activities which are an important aspect of learning, especially learning mathematics. The analysis and theoretical description of the importance of the process of metacognition in solving mathematical problems are presented with two main thoughts. Namely, exposure to mathematical problem-solving activities that are closely related to one's metacognition processes and how metacognition processes take on their role to improve problem-solving skills in learning mathematics. The method used in this study is a literature study. Data collection is done by examining, reading, and drawing conclusions from various sources. The source used is in the form of articles that have been published at least sinta 4 as many as 20 articles. The conclusion from this article is those mathematical problem-solving activities are activities that require optimizing students' metacognition processes. In this case, mathematical problem-solving activities must enable students to be able to optimize declarative, procedural, and conditional knowledge through planning, monitoring, and evaluating students' cognitive processes. Keywords: the process of metacognition, learning mathematics, solving mathematical problems Abstrak Artikel ini bertujuan untuk mendeskripsikan pemecahan masalah matematika dan keterkaitannya dengan proses metakognisi. Penelitian ini menitikberatkan pada kegiatan pemecahan masalah matematika yang merupakan salah satu aspek penting dalam pembelajaran, khususnya pembelajaran matematika. Analisis dan penggambaran teoretis tentang pentingnya proses metakognisi dalam pemecahan masalah matematika disajikan dengan dua pemikiran utama. Yakni, pemaparan mengenai kegiatan pemecahan masalah matematika yang erat kaitannya dengan proses metakognisi seseorang dan bagaimana proses metakognisi mengambil perannya untuk meningkatkan keterampilan pemecahan masalah dalam pembelajaran matematika. Metode yang digunakan dalam penelitian ini adalah studi literatur. Pengumpulan data dilakukan dengan menelaah, membaca dan menarik kesimpulan dari berbagai sumber. Sumber yang digunakan berupa artikel-artikel yang telah di terbit pada jurnal terakreditasi minimal sinta 4 sebanyak 20 artikel. Kesimpulan dari artikel ini adalah kegiatan pemecahan masalah matematika adalah kegiatan yang memerlukan pengaoptimalisian proses metakognisi peserta didik. Dalam hal ini, kegiatan pemecahan masalah matematika harus memungkinkan peserta didik agar dapat melakukan pengoptimalan terhadap pengetahuan declaratif, prosedural, dan kondisional melalui perencanaan, pemantauan, dan evaluasi proses kognisi peserta didik. Kata kunci: proses metakognisi, pembelajaran matematika, pemecahan masalah matematika